Evaluating differential nuclear DNA yield rates and osteocyte numbers among human bone tissue types: A synchrotron radiation micro-CT approach. (May 2017) - Andronowski, Janna M.; Mundorff, Amy Z.; Pratt, Isaac V.; Davoren, Jon M.; Cooper, David M.L.
Highlights: Osteocyte lacunar abundance and density vary between cortical and cancellous bone tissue types. Cortical bone Volumes of Interest contain a higher lacunar abundance and density. Osteocyte lacunar density values are independent of nuclear DNA yield. An alternative explanation likely exists for the higher nuclear DNA yields from cancellous bone. Soft tissue remnants within the medullary cavities may be driving the high nuclear DNA yields. Abstract: Molecular human identification has conventionally focused on DNA sampling from dense, weight-bearing cortical bone tissue, typically from femora or tibiae. A comparison of skeletal elements from three contemporary individuals demonstrated that elements with high quantities of cancellous bone yielded nuclear DNA at the highest rates, suggesting that preferentially sampling cortical bone may be suboptimal (Mundorff & Davoren, 2014). Despite these findings, the reason for the differential DNA yields between cortical and cancellous bone tissues remains unknown. The primary goal of this work is to ascertain whether differences in bone microstructure can be used to explain differential nuclear DNA yield among bone tissue types observed by Mundorff and Davoren (2014), with a focus on osteocytes and the three-dimensional (3D) quantification of their associated lacunae. Osteocytes and other bone cells are recognized to house DNA in bone tissue, thus examining the density of their lacunae may explain why nuclear DNA yield rates differ among bone tissue types. Lacunae were visualized and quantified using synchrotron radiation-based micro-Computed Tomographic imaging (SR micro-CT). Volumes of interest (VOIs) from cortical and cancellous bone tissues (n = 129) were comparatively analyzed from the three skeletons sampled for Mundorff and Davoren's (2014) study. Analyses tested the primary hypothesis that the abundance and density of osteocytes (inferred from their lacunar spaces) vary between cortical and cancellous bone tissue types. Results demonstrated that osteocyte lacunar abundance and density vary between cortical and cancellous bone tissue types, with cortical bone VOIs containing a higher lacunar abundance and density. We found that the osteocyte lacunar density values are independent of nuclear DNA yield, suggesting an alternative explanation for the higher nuclear DNA yields from bones with greater quantities of cancellous bone tissue. The use of SR micro-CT allowed for a scale of analysis that revealed a high range of variation in lacunar abundance in both tissue types. Moreover, high-resolution SR micro-CT imaging revealed potential soft tissue remnants within marrow spaces not visible macroscopically. It is hypothesized that soft tissue remnants observed among the trabeculae of skeletal elements with high quantities of cancellous bone tissue are responsible for the high nuclear DNA yields. These findings have significant implications for bone-sample selection for nuclear DNA analysis in a forensic context when skeletal remains are recovered from the ground surface.